2020
DOI: 10.1177/2472630320922803
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis of Fluorescently Labeled N-Glycans Derived from Biotherapeutics Using an Automated LC-MS-Based Solution

Abstract: Protein glycosylation can impact the efficacy and safety of biotherapeutics and therefore needs to be well characterized and monitored throughout the drug product life cycle. Glycosylation is commonly assessed by fluorescent labeling of released glycans, which provides comprehensive information of the glycoprofile but can be resource-intensive regarding sample preparation, data acquisition, and data analysis. In this work, we evaluate a comprehensive solution from sample preparation to data reporting using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…[47][48][49] With the improvement of the mass spectrometry-based detection method and the automation of data analysis, Zhang and coworkers reported about 90% improvement in throughput compared to conventional manual methods. 47 CE-SDS is another common analytical technique for process sample testing which involves multiple sample preparation techniques such as denaturation, reduction, alkylation, and clean up with significant manual labor. 50 Le et al, reported for the first time an automated CE-SDS sample preparation platform which essentially eliminates all the manual steps such as concentration normalization, removal of salts and other contaminants, and addition of the required CE-SDS reagents.…”
Section: Patmentioning
confidence: 99%
See 2 more Smart Citations
“…[47][48][49] With the improvement of the mass spectrometry-based detection method and the automation of data analysis, Zhang and coworkers reported about 90% improvement in throughput compared to conventional manual methods. 47 CE-SDS is another common analytical technique for process sample testing which involves multiple sample preparation techniques such as denaturation, reduction, alkylation, and clean up with significant manual labor. 50 Le et al, reported for the first time an automated CE-SDS sample preparation platform which essentially eliminates all the manual steps such as concentration normalization, removal of salts and other contaminants, and addition of the required CE-SDS reagents.…”
Section: Patmentioning
confidence: 99%
“…46 Due to the complexity and laborintensive nature of manual glycan analysis methods a variety of sample preparation automation techniques has been reported recently. [47][48][49] With the improvement of the mass spectrometry-based detection method and the automation of data analysis, Zhang and coworkers reported about 90% improvement in throughput compared to conventional manual methods. 47 CE-SDS is another common analytical technique for process sample testing which involves multiple sample preparation techniques such as denaturation, reduction, alkylation, and clean up with significant manual labor.…”
Section: Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Shajahan et al 5 developed a high-throughput method for permethylation of released glycans and propose an automated MSn workflow for the rapid structure characterization of glycoproteins. Zhang et al 6 likewise put forth an efficient high-throughput method for glycomics analysis featuring automated sample preparation, rapid liquid chromatography with fluorescence and mass spectrometric detection, and MS-based target screening for quality control of therapeutic antibody N -glycans. Zhang et al 7 developed O -benzylhydroxylamine (BHA) as a cleavable tag that is both hydrophobic for chromatographic separation of glycans and chromogenic for detection of glycans, in order to obtain sufficient amounts of glycans for functional studies using glycan arrays.…”
Section: Glycomicsmentioning
confidence: 99%
“…Glycan characterization is commonly performed by analysis of glycans released from the protein backbone. As a result of lacking UV absorption chromophores, the release glycans are usually derivatized by introducing fluorescence tags such as 2-aminobenzamide (2-AB) and 2-aminoanthranilic acid (2-AA) to facilitate High-Performance Liquid Chromatography—Fluorescent Detection (HPLC-FLR) [ 10 ]. HPLC-FLR is suitable for profiling and quantitative analysis but is limited for structure identification [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%